1994
DOI: 10.1161/01.res.75.3.556
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis toxin-sensitive G protein mediates coronary microvascular control during autoregulation and ischemia in canine heart.

Abstract: GTP-binding regulatory proteins (G proteins)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
4
7
0
Order By: Relevance
“…[22][23][24] Previous reports from our laboratory have demonstrated that the reactivity of observed vessels to various vasoactive substances or to physiological stimuli is well preserved in this preparation. 11,18,20,25,26 In the present study, the vasodilation of arterial microvessels was also clearly demonstrated when the perfusion pressure was reduced, indicating that the reactivity of the observed vessels was well preserved. The diameters of coronary arterial microvessels at the baseline and at perfusion pressures of 60 mmHg (mild stenosis) and 40 mmHg (severe stenosis).…”
Section: Critique Of Methodssupporting
confidence: 71%
“…[22][23][24] Previous reports from our laboratory have demonstrated that the reactivity of observed vessels to various vasoactive substances or to physiological stimuli is well preserved in this preparation. 11,18,20,25,26 In the present study, the vasodilation of arterial microvessels was also clearly demonstrated when the perfusion pressure was reduced, indicating that the reactivity of the observed vessels was well preserved. The diameters of coronary arterial microvessels at the baseline and at perfusion pressures of 60 mmHg (mild stenosis) and 40 mmHg (severe stenosis).…”
Section: Critique Of Methodssupporting
confidence: 71%
“…PTX has been widely used to block G i and G o proteins (6,16,45,47). Our previous study (32) showed that superfusion of PTX for 2 h effectively blocks ␣ 2receptor-mediated microvascular constriction, which is known to be exclusively mediated by G i protein (32). This result indicated that superfusion of PTX for 2 h is sufficient to block G PTX of epicardial microvessels.…”
Section: Critique Of Methodsmentioning
confidence: 93%
“…When the oxygen supply to the myocardium is suppressed, coronary arteries dilate via the activation of ATP-sensitive K ϩ (K ATP ) channels, as observed in hypoxemia (8), hypoperfusion (7,30,40), and reactive hyperemia (3,25). In addition to these observations, we have previously demonstrated that pertussis toxin (PTX)-sensitive G protein (G PTX ) plays a crucial role in the canine coronary microvascular regulation of vasomotor tone during hypoperfusion in vivo (32).…”
mentioning
confidence: 95%
“…4,5,13,14 Briefly, the dogs were anesthetized and ventilated. A thoracotomy was performed, and the pericardium was cut to expose the heart surface.…”
Section: Beating-heart Preparationmentioning
confidence: 99%
“…3 Previous in vivo studies have shown that G PTX proteins are critical in the microvascular control during autoregulation and metabolic stimulation. 4,5 Hypercholesterolemia is one of the most important coronary risk factors. Although morphological changes like plaque formation take place only in conduit vessels, various functional changes are known to extend to the coronary microvessels.…”
mentioning
confidence: 99%